Effects of Picture Books Intervention on Language Learning Skills of Pupils with Learning Disabilities in Jos, Plateau State - Gwanshak, Nandi Abani (NIU Journal of Humanities, 2020)
This study examined the effects of picture books on language learning skills of pupils with learning disabilities. Quasi experimental research design was adopted for the study; specifically, the non-equivalent pretest-posttest control group design was used. The population of the study comprised of seventy eight primary two pupils with learning disabilities. Purposive sampling technique was used to select forty pupils as sample for the study. An adapted Functional Diagnostic Test of Language Assessment Instrument (FDTLA) and Assessment of Language Ability (ALA) score sheet were used to collect data which helped to answer the research questions and test the hypotheses raised. Data for the research was collected through administration of pretest on the experimental and control groups. After the pretest, the experimental group was exposed to an intervention using picture books, while the control group was taught using the conventional oral method in their regular classroom. Two research questions were answered using mean scores. Three hypotheses were formulated and two were tested using t-test for independent samples at 0.05 level of significance and one hypothesis was tested using ANCOVA. The results showed that picture books improved the language skills of the pupils significantly as shown in the performance of the experimental group who were subjected to an intervention using picture books as against pupils (control group) who were taught using the conventional method. In the same vein, the results also showed that there was no significant difference between the language learning skills of boys and girls after exposure to picture books. Keywords:   Picture Book, Intervention, Language Skills, Pupils with Learning Disabilities